PRESIPITASI LOGAM BERAT LIMBAH CAIR LABORATORIUM MENGGUNAKAN NATRIUM SULFIDA DARI BELERANG ALAM - Wisni Rona Anami; Mamay Maslahat; Dian Arrisujaya (Universitas Nusa Bangsa, 2020)
Precipitation of Laboratory Wastewater Heavy Metals by Natural Sulphur Sodium Sulfide Sodium sulfide (Na2S) from natural sulfur has been used for heavy metal precipitation from laboratory wastewater. Heavy metals in laboratory wastewater include mercury (Hg), lead (Pb), chromium (Cr) and zinc (Zn). Initial laboratory wastewater testing was performed by measuring the initial pH and the concentration of heavy metals in the wastewater prior to precipitation using the atomic absorption spectrophotometer. Sulphide precipitation phase consists of variations in the concentration of NaOH, time, temperature, and volume of dissolving Na2S. Parameters for the efficiency of Hg, Pb, Zn and Cr heavy metal precipitation were the initial pH, concentration and rate of stirring of the solution. Results showed that the optimum precipitation efficiency for Zn is achieved by using 10 % Na2S solution with an efficiency of 97.93 %. The most significant reduction in Cr and Hg was the use of 20 % Na2S solution with a precipitation efficiency of 99.24 % and 99.76 % respectively. The optimal efficiency for Pb with a 30 % Na2S solution was 99.68 %. Natural sulfur can reduce the levels of heavy metals in laboratory wastewater by precipitation.Key words: Natural sulfur, Heavy metals, Precipitation, Sodium sulfide, ABSTRAKPresipitasi logam berat dari limbah cair laboratorium telah dilakukan dengan menggunakan natrium sulfida (Na2S) dari belerang alam. Logam berat yang terkandung dalam limbah cair laboratorium diantaranya adalah merkuri (Hg), timbal (Pb), kromium (Cr) dan seng (Zn). Pengujian awal limbah laboratorium dilakukan dengan mengukur pH awal dan kadar logam berat yang terdapat dalam limbah sebelum presipitasi menggunakan pH meter dan spektrofotometer serapan atom. Tahapan presipitasi limbah oleh sulfida meliputi pembuatan variasi konsentrasi NaOH, waktu, suhu, dan volume pelarutan Na2S. Parameter efisiensi presipitasi logam Hg, Pb, Zn, dan Cr meliputi pH, Konsentrasi dan Kecepatan pengadukan. Hasil penelitian menunjukkan efisiensi pengendapan optimal untuk logam Zn terdapat pada penggunaan larutan Na2S 10% dengan efisiensi 97,93%. Larutan Na2S 20% paling banyak menurunkan logam Cr dan Hg dengan efisiensi masing-masing sebesar 99,24% dan99,76%. Efisiensi optimal untuk logam Pb berada pada penggunaan larutan Na2S 30% dengan efisiensi 99,68%. Belerang alam mampu menurunkan kadar logam berat dalam limbah cair laboratorium dengan metode presipitasi.Kata kunci: Belerang alam, Logam berat, Presipitasi, Natrium sulfida